1993
DOI: 10.1017/s0952523800006167
|View full text |Cite
|
Sign up to set email alerts
|

Visual and vestibular reflexes that stabilize gaze in the chameleon

Abstract: Spontaneous eye movements as well as visual, vestibular, and proprioceptive cervical reflexes which contribute to gaze stabilization were investigated in the chameleon using the magnetic search-coil technique. The oculomotor range of each eye was very large (180 deg horizontally x 80 deg vertically). Spontaneous ocular saccades were independent in the two eyes and could have very large amplitudes. The fast phases of nystagmus during the stabilization reflexes were also independent in the eyes. In the head-rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
5
22
0
Order By: Relevance
“…In accordance with our results, Bloch and colleagues describe converging binocular saccades towards frontally presented stimuli in pigeons, but in contrast to our results in zebra finches, the pigeons reacted to lateral stimulation with only one attending eye, the other eye showing no coordinated movements (Bloch et al, 1986). The pigeon results are in accordance with observations in chameleons where left and right eyes are synchronized during prey tracking (Ott, 2001), and spontaneous eye movements can be independent in direction and amplitude (Gioanni et al, 1993). In contrast, zebra finches only use one eye to move towards a target after stimulation in both lateral visual fields.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our results, Bloch and colleagues describe converging binocular saccades towards frontally presented stimuli in pigeons, but in contrast to our results in zebra finches, the pigeons reacted to lateral stimulation with only one attending eye, the other eye showing no coordinated movements (Bloch et al, 1986). The pigeon results are in accordance with observations in chameleons where left and right eyes are synchronized during prey tracking (Ott, 2001), and spontaneous eye movements can be independent in direction and amplitude (Gioanni et al, 1993). In contrast, zebra finches only use one eye to move towards a target after stimulation in both lateral visual fields.…”
Section: Discussionsupporting
confidence: 93%
“…Dieringer et al (1983) examined eye and head contributions to gaze stability in frogs and turtles and determined that the head played a major role in stabilization (Ͼ80%), with the eyes only being used in a transient manner. In chameleons, which also happen to have a very large oculomotor range, undercompensatory gaze was observed during rotational motion, with the head once again contributing the major response component (Gioanni et al 1993). Collewijn (1977) noted similar results in rabbits to those observed in our study, with VCR gains during head-free conditions to reach near unity in the dark, with a small eye movement component.…”
Section: Different Behavioral Strategies For Gaze Stabilizationsupporting
confidence: 87%
“…Eye movements in response to head motion have been extensively studied in a variety of vertebrate species ranging from fish to primates (Escudero et al 1993). In lateral-eyed species, such as frogs (Dieringer and Precht 1982), lizards (Gioanni et al 1993), rabbits (Baarsma and Collewijn 1974), chinchillas (Merwin et al 1989), and guinea pigs (Escudero et al 1993), eye movements in response to motion when the head is fixed have largely been shown to be undercompensatory. For example, in pigeons, we recently found that the three-dimensional (3-D) vestibuloocular (VOR) responses to both rotational and linear motion were significantly undercompensatory in gain (Dickman and Angelaki 1999;Dickman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support the existence of a monocularly organised oculomotor system in sharks (Maxwell, 1920;Masseck and Hoffmann, 2008). Monocular organisation is more common in animals with laterally positioned eyes as described for some teleost fishes [sandlance, Lymnichthyes fasciatus, and pipefish, Corythoichthyes intestinalis (Fritsches and Marshall, 2002;Pettigrew et al, 1999)] and the chameleon, Chamaleo chamaleo (Gioanni et al, 1993;Pettigrew et al, 1999). The contralateral placement of the medial rectus motor neurons in the midbrain of sharks differs from most vertebrates, which may allow eye movements to be controlled independently (Graf and Brunken, 1984).…”
Section: Eye Movements In Sharkssupporting
confidence: 87%